Predpisovanje telesne aktivnosti za preprečevanje bolezni srca in ožilja - Fras, Zlatko (Zdravstveno varstvo, 2002)
Regular motion represents and is understood as an important health protective factor and we are using it as an integral part of treatment in many disease states. Few basic recommendations for physical activity prescription are presented. It is moderate physical activity which is enough for important positive effects on people's health. Both patients and also healthy individuals should be prescribed with those types of motion they like most, those most easily incorporated into everyday life and appropriate regarding individual's physical capacity, age and health profile. Before the prescription individual's health profile should be assessed. For the proper physical activity prescription in primary prevention there is a general recommendation, that the most appropriate is regular, moderate activity. The principle of balanced prescription of various types of activity should be followed, with SO% of aerobic activity and 25% of both resistant and flexibility exercises. Every exercise prescription for each type of activity should consist of frequency, intensity and also rate of progression in regularactivity programme. The most appropriate positive influence on adoptionof active lifestyle represent population oriented intervention programmes incorporating influences on more than one risk factors at the same time. It was also proved that physical activity protects health in all age groups. Special attention must be paid to the end of adolescence, because it is clear that most of the people stop physical activity at this point and acquire sedentary lifestyle.
Keywords: Cardiovascular diseases; Death, sudden, cardiac; Exercise; Exercise test; Exertion; Health status; Heart rate; Kardiovaskularne bolezni; Napor; Obremenitveni test; Physical endurance; Prevention and control; preventiva; Smrt nenadna, srčna; Srce, frekvenca; telesna aktivnost; Telesna vaja; Telesna vzdržljivost; Zdravstveno stanje